DOI: 10.11606/t.17.2020.tde-13042020-144056
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da massa muscular e da presença de sarcopenia em idosos oncológicos e sua associação com a avaliação geriátrica ampla

Abstract: MATTOS, C. H. P. S. 2019. Evaluation of muscle mass and presence of sarcopenia in older cancer patients and its association with comprehensive geriatric assessment. 92f. Thesis (Ph.D.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…Recent data on the psychometric properties of the Portuguese version of the GDS-15 was reported by Matos et al (2019). The authors found that the scale presented good internal consistency (α = 0.85) and discriminant validity (the global score differentiated individuals with emotional disorders) (Matos et al, 2019). Consistent with these previous results, the internal reliability analysis of this measure yielded a Cronbach's α coefficient of 0.82.…”
Section: Geriatric Depression Scale Short Form (Gds-15)supporting
confidence: 57%
See 1 more Smart Citation
“…Recent data on the psychometric properties of the Portuguese version of the GDS-15 was reported by Matos et al (2019). The authors found that the scale presented good internal consistency (α = 0.85) and discriminant validity (the global score differentiated individuals with emotional disorders) (Matos et al, 2019). Consistent with these previous results, the internal reliability analysis of this measure yielded a Cronbach's α coefficient of 0.82.…”
Section: Geriatric Depression Scale Short Form (Gds-15)supporting
confidence: 57%
“…The authors also found that the GDS-15 was a reliable screening instrument for major depression according to ICD-10 (International Classification of Diseases, 10th revision) and DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, 4th edition), and a reliable measure of the severity of depressive episodes (Almeida and Almeida, 1999a). Recent data on the psychometric properties of the Portuguese version of the GDS-15 was reported by Matos et al (2019). The authors found that the scale presented good internal consistency (α = 0.85) and discriminant validity (the global score differentiated individuals with emotional disorders) (Matos et al, 2019).…”
Section: Geriatric Depression Scale Short Form (Gds-15)mentioning
confidence: 93%
“…Estes resultados são importantes na validação do construto e implementação de políticas com o objetivo de influenciar a qualidade de vida subjetiva dos idosos e ampliar o corpo de conhecimento sobre os fatores que afetam a satisfação com a vida. Encontrados novos e significativos valores estatísticos sobre a validade do constructo a partir de Apóstolo et al ( 2014) e de Matos et al (2019) numa boa consistência interna (α = .85). Foram encontrados valores estatísticos mais robustos de consistência da Escala relativamente ao estudo de Neto (1993) com consistência interna de α = .78 versus atual α= .962.…”
Section: Discussionunclassified